Gender difference in Attention deficit hyperactivity disorder among adolescents in Iceland - Áslaug María Agnarsdóttir 1995- (2018)
Attention deficit hyperactivity disorder (ADHD) is a neurodevelopmental disorder which consists of symptoms of inattention and hyperactivity-impulsivity. ADHD can have a significant impact on well-being, academic achievement, and communication of children and adolescents. Previous studies showed that ADHD was more common among boys rather than girls. However, girls showed more inattention symptoms of ADHD. In the current study, gender differences on ADHD diagnosis and medication were examined. Gender differences in symptoms manifestation of inattention, hyperactive-impulsive and combined type of ADHD were also examined, also if boys are overdiagnosed and if girls are underdiagnosed. Also, were measured whether ADHD affected school performance. The participants were students in all elementary schools in Iceland and were in 8th, 9th and 10th grade. The data in the study was from ICSRA. The results showed that there was no significant gender difference in meeting the screening for the combined and the inattentive type of ADHD, but more boys met screening for the hyperactive-impulsive type. Significantly more boys than girls said they were diagnosed with ADHD and received medication for ADHD. The results also showed that ADHD had an impact on school performance. Keywords; gender differences; adolescents; ADHD; combined type; inattention; hyperactivity; impulsivity; overdiagnoses; underdiagnoses; school performance. Athyglisbrests- og ofvirkniröskun (ADHD) er taugaþroskaröskun sem samanstendur af einkennum athyglisbrests og/eða ofvirkni og hvatvísi. ADHD getur haft veruleg áhrif á árangur í skóla eða vinnu, líðan og samskipti barna og unglinga. Fyrri rannsóknir sýna að ADHD sé algengara meðal stráka en að stelpur sýni meiri einkenni af athyglisbrest. Í þessari rannsókn var kynjamunur á ADHD greiningum og lyfjameðferðum skoðaður. Kynjamunur á birtingamynd einkenna á athyglisbrests- og ofvirkni-hvatvísis- og blandaðari gerð ADHD var einnig skoðaður, og hvort strákar séu ofgreindir, stelpur séu vangreindar. Einnig var ...